IDENTIFICATION OF ASPERGILLUS SP GROWTH ON WHITE BREAD AGAINST STORAGE TEMPERATURE - Fitri Rahmi Fadhilah; Liah Kodariah (Jurnal Kesehatan Rajawali, 2020)
Bread is a kind of food consumed by the Indonesian people. the composition of in bread is one of the sources of nutrition microorganisms that are important in growth, especially the Aspergsillus sp. the objective of this study to identify the growth of Aspergillus sp. on bread to temperature storage at room temperature 25oC -37oC and cold temperature 4oC-10oC. The methodology used is a descriptive method. By using four samples of white bread sold in Burung Tungku market which is stored at room temperature and cold temperatures. the research was done in a Microbiologi laboratory of STIKes Rajawali Bandung. The result of this research showed that the growth of Aspergillus sp in white bread grew faster at room temperature than on cold temperatures. Room temperature of 25C- 37C Aspergillus sp began to grow on the 4th day. While at the cold temperature of 4C- 10C Aspergillus sp began to grow on the 10th day. From the result of the study, it can be concluded that the inhibition of fungal growth can be caused by several factors, namely temperature and humidity factors. which are less than optimal. The optimum temperature of Aspergillus is 25C- 37C with relative humidity (RH)